Medical Decision Style and COVID-19 Behavior. (August 2022) - Tinghög, Gustav; Strand, Liam
Given the flood of health-related information stirred up by the coronavirus disease 2019 (COVID-19) pandemic, it is important to understand the factors that influence people to engage in protective public health measures so that medical communication can be tailored to be effective. Following the idea that people have a general inclination toward health care utilization, which is either more passive (i.e., medical minimizer) or more aggressive (i.e., medical maximizer), we assess if this inclination extends to being more or less willing to engage in protective public health behavior. We investigate the effect of individual differences in medical minimizing and medical maximizing orientation on COVID-19–related protective behaviors and attitudes. We used the validated Medical Maximizer-Minimizer Scale (MMS) and surveyed a diverse opt-in sample of the Swedish population ( n = 806). Our results show that the MMS significantly predicts a wide range of self-reported behaviors and attitudes in relation to COVID-19. Participants with a stronger minimization orientation were significantly less likely to practice social distancing, follow hygiene recommendations, and be supportive of strict COVID-19 policies. Participants with a stronger maximization orientation had a larger discrepancy between perceived own risk and others getting infected. Thus, they perceived themselves as being less at risk for getting infected compared to the average person. Our findings imply that the MMS can be effectively used to predict who is more or less reluctant to follow public health recommendations. JEL codes : D70 E71 I12 I18 Graphical Abstract This is a visual representation of the abstract.